Features of political culture of Japan and CHina - Orazbekova, G R; Turgenbay, А А (Journal of Oriental Studies, 2016)
This article discusses the features of political culture of Japan and China, as well as unique national traditions and processes of modernization and Westernization. The political culture of Japan, especially the development of its history and culture as well as other countries are characterized. The current political culture of China is based on the Chinese styled «market socialism», on «Chinese national idea», synthesis of legistic and Confucian traditions.